Early β-Amyloid-induced Synaptic Dysfunction Is Counteracted by Estrogen in Organotypic Hippocampal Cultures - Merlo, Sara; Federica Spampinato, Simona; Capani, Francisco; Angela Sortino, Maria (Current Alzheimer Research, 2016)
In the present study we set up a model of slow progression of neuronal injury by exposing organotypic hippocampal cultures to a low concentration of Amyloid β (25-35) peptide (Aβ, 2 μM) to analyze the time-related effects of 17-β estradiol (17β-E2, 10 nM). Neuronal death occurs after 7 d and is prevented by addition of 17β-E2 24 h prior to, together with or 48 h after exposure to Aβ. This effect is mimicked by selective ERα agonist PPT (100 nM). Treatment with Aβ leads to early and transient (16-72 h) increase of pre- and post-synaptic proteins synaptophysin and PSD95, followed by a decrease coincident with neuronal death (7d), all prevented by 17β-E2. At 72 h of Aβ exposure, synaptic activity is increased, as by higher levels of glutamate and increased loading and unloading of FM 1-43-labeled synaptic vesicles. All these effects are also prevented by 17β-E2. These data point out beneficial effects of estrogen on early Aβ-induced synaptic disruption.
Keywords: Alzheimer’s Disease